LENGTH-WEIGHT RELATIONSHIP AND RELATIVE CONDITION OF NOTOPTERUS NOTOPTERUS (PALLAS) FROM EAST KOLKATA WETLANDS, WEST BENGAL - CHOUDHURY, SAMPURNA ROY; DAS, SUDHIR; SAHOO, A. K.; BEHERA, B. K. (Journal of the Inland Fisheries Society of India, 2021)
The East Kolkata Wetlands, situated between 22°25' - 22°40' N and 88°20' - 88°35' E (Fig. 1) with an area of 12500 ha produce 11 thousand metric tonnes of fish annually (Chattopadhyay et al., 2002). Indian featherback, Notopterus notopterus, forms an important fishery in these wetlands. The study investigated the length-weight relationship and relative condition of N. notopterus (Pallas, 1769) from East Kolkata wetlands.